2001
DOI: 10.1152/ajprenal.2001.280.4.f592
|View full text |Cite
|
Sign up to set email alerts
|

Chronic NOS inhibition reverses systemic vasodilation and glomerular hyperfiltration in pregnancy

Abstract: The chronic role of nitric oxide (NO), independent of prostaglandin synthesis, in the primary peripheral vasodilation, increased glomerular filtration rate (GFR), and renal plasma flow (RPF) in normal pregnancy remains to be defined. The purpose of the present study was to chronically inhibit NOS to return systemic vascular resistance (SVR), cardiac output (CO), GFR, and RPF to nonpregnant values. Pregnant rats received the nitric oxide synthase (NOS) inhibitor, nitro-L-arginine methyl ester (L-NAME), orally f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 38 publications
1
54
0
Order By: Relevance
“…The proposed mechanism of relaxin involves an increase in vascular gelatinase activity, which upregulates NO-dependent vasodilation via the endothelin-B NO pathway (14). In pregnant rats, investigators have convincingly demonstrated increments in endogenous production of NO (15), and through acute or chronic inhibition of NO synthase, investigators have demonstrated abolishment of the glomerular hyperfiltration in pregnancy (16,17). Hence, NO is necessary for the hemodynamic adaptation in renal function during pregnancy, and relaxin may represent a pregnancy-specific mechanism for augmenting the effects of NO.…”
Section: Renal Functionmentioning
confidence: 99%
“…The proposed mechanism of relaxin involves an increase in vascular gelatinase activity, which upregulates NO-dependent vasodilation via the endothelin-B NO pathway (14). In pregnant rats, investigators have convincingly demonstrated increments in endogenous production of NO (15), and through acute or chronic inhibition of NO synthase, investigators have demonstrated abolishment of the glomerular hyperfiltration in pregnancy (16,17). Hence, NO is necessary for the hemodynamic adaptation in renal function during pregnancy, and relaxin may represent a pregnancy-specific mechanism for augmenting the effects of NO.…”
Section: Renal Functionmentioning
confidence: 99%
“…Estrogens are known to upregulate nitric oxide (NO) synthase, 2 and there is experimental evidence that NO contributes to this arterial vasodilation during pregnancy. 3,4 Moreover, an increase in circulating relaxin during early pregnancy is also known to increase NO-mediated arterial vasodilation. 5 Systemic arterial vasodilation in pregnancy is associated consequently with a secondary increase in cardiac output.…”
mentioning
confidence: 99%
“…Estrogen upregulates endothelial nitric oxide synthase in pregnancy, and inhibitors of nitric oxide synthesis normalize the systemic and renal hemodynamics in rat pregnancy. 21 On the background of this unifying mechanism of body fluid volume regulation by the kidney, the clinical use of the term "decreased effective blood volume" can be considered outdated and be replaced by "arterial underfilling." However, if the use of the term persists in clinical medicine, then it should be "decreased effective arterial blood volume.…”
mentioning
confidence: 99%